2018
DOI: 10.1007/s00167-018-5013-4
|View full text |Cite
|
Sign up to set email alerts
|

A polygon-shaped complex appearance of medial patellofemoral ligament with dynamic functional insertion based on an outside-in and inside-out dissection technique

Abstract: The medial patellofemoral ligament which dissected a complicated structure with bony and non-bony attachment and multi-connected to neighboring structures on both patella and femur side appears as a polygon-shaped complex structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…52 Most of the studies in the last 2 years are in agreement that the MPFC attaches more proximally than we thought, having a connection to the medial border of the vastus intermedius tendon (Table 1). 40,41,[43][44][45]47,49,50 My colleagues and I performed a cadaveric dissection and found similar findings; that MPFC originates from a midpoint between the femoral epicondyle and adductor tubercle. It fans out into 2 bands: a main thick band to the upper half of the patella and a thin upper layer running anteriorly, upward, then under the vastus medialis obliquus.…”
mentioning
confidence: 63%
“…52 Most of the studies in the last 2 years are in agreement that the MPFC attaches more proximally than we thought, having a connection to the medial border of the vastus intermedius tendon (Table 1). 40,41,[43][44][45]47,49,50 My colleagues and I performed a cadaveric dissection and found similar findings; that MPFC originates from a midpoint between the femoral epicondyle and adductor tubercle. It fans out into 2 bands: a main thick band to the upper half of the patella and a thin upper layer running anteriorly, upward, then under the vastus medialis obliquus.…”
mentioning
confidence: 63%
“…The preparation was held from the inside of the joint because during the pilot anatomical preparations, we found that it was easier to access the MPFL without injury, as the third layer is less attached to the second layer than the first, and as soon as the capsule was detached we came into direct contact with the MPFL, either by direct vision or by palpation [24].…”
Section: Discussionmentioning
confidence: 99%